Pengaruh Moralitas Individu, Budaya Organisasi, Dan Pengendalian Internal Terhadap Kecurangan Akuntansi - Rahandhika Ivan Adyaksana; Lia Nadia Sufitri (Akmenika: Jurnal Akuntansi dan Manajemen, 2022)
Fraud cases have always been the subject of fierce debate, especially with the emergence of cases that occurred in Indonesia, especially the latest ACFE resport regarding fraud case schemes that often accur in Indonesia in 2019. Overall,the purpose of this research is to examine individual studies of ethics, organizational culture and internal controls towards accountingÂ  farud. The population of this study are civil servants (PNS) and ordinary daily workers (THL) who work at the BKAD office in the DIY sector. The sample of this research is 80 people. The sampling method in this research is random sampling. The dataÂ  used in this research were carried out as primary data by directly visiting the BKAD secretariat and distributing questionnaires. The treatment method used is multiple linear regression. Based on the result of the research, it can be concluded that the variables of personal ethics (X1), organizational culture (X2), and internal control (X3) have a negative effect on accounting fraud (Y).